2020
DOI: 10.1161/circresaha.120.317578
|View full text |Cite
|
Sign up to set email alerts
|

Association of Habitual Physical Activity With Cardiovascular Disease Risk

Abstract: Rationale: A sedentary lifestyle is associated with increased risk for cardiovascular disease (CVD). Smartwatches enable accurate daily activity monitoring for physical activity measurement and intervention. Few studies, however, have examined physical activity measures from smartwatches in relation to traditional risk factors associated with future risk for CVD. Objective: To investigate the association of habitual physical activity measured by smartwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 35 publications
1
25
2
Order By: Relevance
“…[8][9][10][11][12] Large-scale observational studies have shown that the MyDataHelps app is user friendly and enables high-fidelity data collection. [13][14][15] Participants were asked to wear their watch for 12 h per day or longer and to do daily or weekly tasks, including home blood pressure measurement.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11][12] Large-scale observational studies have shown that the MyDataHelps app is user friendly and enables high-fidelity data collection. [13][14][15] Participants were asked to wear their watch for 12 h per day or longer and to do daily or weekly tasks, including home blood pressure measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Physical exercise attenuates cardiovascular risk factors ( Lin et al, 2020 ). Studies on the effects of exercise on cardiac remodeling have shown an improvement in contractility, prevention of apoptosis, and attenuation of myocardial fibrosis and LV adverse remodeling ( Huang et al, 2012 ; Locatelli et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the remaining 1948 participants who were enrolled in the eFHS, 1185 chose to participate with the Apple Watch and returned step data between November 2016 and January 2019. We excluded 213 participants who either wore the smartwatch less than 5 hours on any given day or those who returned smartwatch data for less than 30 days during the study period because these participants did not meet the definition for habitual PA previously published [ 27 ]. We also excluded 135 participants who did not attend the 3 examinations needed to build the BMI trajectory, participants with BMI values <18.5 or >60 kg/m 2 at any of the 3 research examinations, and participants who had a gastric bypass procedure.…”
Section: Methodsmentioning
confidence: 99%